Improving Human Resource Management through Work Structuring, Training in Marketing and Operations at PT. Intan Rahmadhani Santosa - Ramadhani, Hilwa; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The internship at PT Intan Rahmadhani Santosa aims to address operational and product marketing challenges through digital strategies. This involved needs analysis, strategic planning, implementation of training programs, and evaluation of results. The results achieved included the development of detailed SOPs, establishment of company regulations, Canvas training for digital marketing, and Google Sheets training for inventory management. These programs improved operational efficiency, enhanced product marketing through digital media, and improved employee skills in inventory management and reporting. Overall, this internship program successfully provided solutions to improve the performance and long-term growth of PT Intan Rahmadhani Santosa amidst competitive market conditions.